Penyandian Pesan Hybrid dengan Myszkowski Cipher dan Rivest, Shamir, Adleman (RSA) - Safitri, Sukmawati Indah; Khudzaifah, Muhammad; Jauhari, Mohammad Nafie (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2023)
Classical and modern cryptography have advantages and disadvantages in securing text messages. Hybrid algorithms can combine two algorithms to produce a higher level of message security when compared to one type of algorithm. This study discusses a hybrid algorithm that combines Myszkowski Cipher and RSA. The purpose of this research is to obtain ciphertext that is more difficult to crack by cryptanalysis. The hybrid algorithm process is done by encrypting text messages with the Myszkowski Cipher algorithm then the key used in the Myszkowski Cipher algorithm are encrypted using the RSA algorithm with the equation . Then the ciphertext and cipherkey will be obtained in numerical. The decryption process is done by decrypting the cipherkey by specifying the value of as the private key so that using the equation . Next is by trying the value of until a value is obtained, after which decryption to the equation , then the process of decrypting ciphertext using Myszkowski Cipher can be done. The benefit of this research is can improve the security of messages because it applies the advantages of each algorithm in its encoding.